ChemInform Abstract: An Efficient Route to Novel Uracil‐Based Drug‐Like Molecules. Issue 38 (3rd September 2015) - Babkov, Denis A.; Chizhov, Alexander O.; Khandazhinskaya, Anastasia L.; Corona, Angela; Esposito, Francesca; Tramontano, Enzo; Seley‐Radtke, Katherine L.; Novikov, Mikhail S.
Abstract Numerous benzophenone‐derived uracil derivatives are prepared and evaluated towards their inhibition of the RNA‐dependent DNA‐polymerase activity of HIV‐1 reverse transcriptase.